Carbonaceous and ionic components in ultrafine and fine particles at four sampling sites in the vicinity of roadway intersection - Kim, Kyung Hwan; Sekiguchi, Kazuhiko; Kudo, Shinji; Kinoshita, Masatoshi; Sakamoto, Kazuhiko (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Ultrafine particles (UFPs; Dp < 0.1 mu m) and fine particles (FPs; Dp < 2.5 mu m) were simultaneously collected for 11 h periods in the daytime and in the nighttime at four sites (S1-S4) around a roadway intersection in an urban area. Sampling was carried out for 14 consecutive days to determine the effect of the intersection on the chemical composition of atmospheric UFPs and FPs. The relative contributions of organic carbon (OC) and elemental carbon (EC) to total carbon (TC) in the daytime samples were 65-86% (UFPs: 83-86%; FPs: 65-75%) and 14-35% (UFPs: 14-17%; FPs: 25-35%), respectively, whereas those in the nighttime samples accounted for 71-90% (UFPs: 87-90%; FPs: 71-78%) and 10-29% (UFPs: 10-13%, FPs: 22-29%), respectively, indicating that the contribution of EC in both UFPs and FPs was higher during the daytime. The decrease in the concentration of carbonaceous components with distance from the intersection indicated a strong effect of motor vehicles emissions on the composition of UFPs and FPs around the intersection. The diurnal variations of sulfate and nitrate in UFPs are consistent with the seasonal variations of sulfate and nitrate in FPs showing higher sulfate and nitrate concentrations in summer and winter, respectively. Not observed in FPs, the diurnal patterns of sulfate and nitrate in UFPs may be closely related to particle size in comparison with larger particles, because smaller particles are more strongly affected by the surrounding environment, for example, through oxidation and dissociation. The present study provides interesting observation that the emission characteristics of OC and EC fractions can be different in the same roadside environment depending on the distance from roadway intersection and particle sizes. Furthermore, concentration difference between EC and black carbon (BC) was found at specific site indicating different EC emission characteristics at the same roadside environment. (C) 2013 Elsevier Ltd. All rights reserved.